2017
DOI: 10.1186/s12884-017-1345-1
|View full text |Cite
|
Sign up to set email alerts
|

On predicting time to completion for the first stage of spontaneous labor at term in multiparous women

Abstract: BackgroundLabor that progresses faster than anticipated may lead to unplanned out-of-hospital births. With the aim to improve planning of transportation to birthing institutions, this study investigated predictors of time to completion for the first stage of labor conditional on cervical opening (conditional time) in multiparous women at term.MethodsWe performed a retrospective analysis of partograms for women in Robson’s group 3 who delivered at one hospital from 2003 to 2013. A generalized additive mixed mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
(58 reference statements)
2
15
0
Order By: Relevance
“…These imply no risk for cephalopelvic disproportion, resulting in normal progress of labor [26]. One study has also supported the notion that the higher the birthweight the higher the duration of labor [27].…”
Section: Discussionmentioning
confidence: 89%
“…These imply no risk for cephalopelvic disproportion, resulting in normal progress of labor [26]. One study has also supported the notion that the higher the birthweight the higher the duration of labor [27].…”
Section: Discussionmentioning
confidence: 89%
“…Gunnarsson et al . evaluated retrospectively 1753 term parous women who had spontaneous labor and found that maternal body mass index, neonatal birth weight and epidural and syntocinon use contributed to prediction of time to complete the first stage of labor. Masturzo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nesheim analyzed 5418 women in labor to assess the contribution of a variety of factors in predicting duration of labor, and found that the most significant predictors were nulliparity, induction vs spontaneous labor, neonatal birth weight, maternal height, gestational age and occipital position, but did not report overall variance 43 . Gunnarsson et al evaluated retrospectively 1753 term parous women who had spontaneous labor and found that maternal body mass index, neonatal birth weight and epidural and syntocinon use contributed to prediction of time to complete the first stage of labor 44 . Masturzo et al examined 270 women in spontaneous second stage of labor and reported that the highest quartile for AoP had the shortest mean time to delivery 45 .…”
Section: Comparison With Findings From Previous Studiesmentioning
confidence: 99%
“…Whether labor is induced or spontaneous, its progression is slower in nulliparous women compared to multiparous women. (17)(18)(19) Women with preterm pregnancies (gestational age less than 37 weeks) were more likely to have delayed onset of active labor, In a relatively similar study done in Uganda, induction-delivery time, a fair indicator of labor progression, reduced with increasing gestational age. (20).…”
Section: Discussionmentioning
confidence: 99%